The bad education. The Spanish Transition in High School Textbooks - Tappi, Andrea; Tébar Hurtado, Javier (Historia y Memoria de la Educación, 2024)
We present the results of an investigation on how the Spanish Transition is treated in History textbooks used in the 2nd year of the Baccalaureate level, during the LOMCE stage, between 2013 and 2022. We adopt the framework of research that focuses on the analysis of the content and the form of historical discourse in textbooks, within the scope of the purposes indicated by Jörn Rüsen: to determine with what delay academic debate reaches textbooks, to know what application is made of historical knowledge and, finally, to decipher the messages transmitted in the field of political education. Our objective is to demonstrate that textbooks address the Transition with an institutional approach that enhances its consensual character and minimizes the dimension of social conflict and of social agents. Thus, the texts do not provide students with adequate knowledge of the complex genesis of the current parliamentary regime; but neither do they convey the idea that a democracy is the result of the dialectic between the social actors involved. Therefore, it is necessary to develop and facilitate critical tools, from the field of History, that will allow students to better engage as citizens of a participatory political system.